Beta-Lactam Antibiotics Inhibit Agonist-Stimulated Platelet Calcium Influx - Burroughs, Susan F; Johnson, Gerhard J (Thrombosis and Haemostasis, 1993)
(β-lactam antibiotics cause platelet dysfunction with reversible agonist-receptor inhibition, irreversible [14C]-penicillin binding, and inhibition of agonist-stimulated elevation in cytosolic Ca2+ ([Ca2+]i), occurring after 24 h exposure in vitro and after in vivo treatment. We investigated β-lactam antibiotic-induced inhibition of rises in [Ca2+]i stimulated by thrombin, sodium arachidonate or A23187 to determine whether Ca2+ influx or intracellular release was primarily affected. The mean rise in [Ca2+]i, measured with fura-2-AM, was inhibited 43.7-84.1% by penicillin when the extracellular Ca2+ concentration ([Ca2+]e) was 1 mM, but was significantly less inhibited when [Ca2+]e was <1 μM. NiCl2 (2 mM), that blocks Ca2+ influx, caused inhibition comparable to penicillin. MnCl2 (1 mM), that quenches the intracellular fura-2 signal, significantly decreased the rise in 1 mM [Ca2+]i when [Ca2+]e was 1 mM, but did not increase the inhibition caused by penicillin. Penicillin did not inhibit the rise in [Ca2+]i stimulated by inositol-1,4,5-trisphosphate or GTPγS. Therefore, β-lactam antibiotics inhibit agonist-induced elevations of [Ca2+]i primarily through inhibition of Ca2+ influx, which probably accounts for the irreversible inhibition of platelet function seen after prolonged in vitro or in vivo treatment.